The safety of live attenuated influenza vaccine in children and adolescents 2 through 17 years of age: A Vaccine Safety Datalink study. Issue 1 (17th November 2017) - Daley, Matthew F.; Clarke, Christina L.; Glanz, Jason M.; Xu, Stanley; Hambidge, Simon J.; Donahue, James G.; Nordin, James D.; Klein, Nicola P.; Jacobsen, Steven J.; Naleway, Allison L.; Jackson, Michael L.; Lee, Grace; et al.
Abstract: Purpose: To evaluate the safety of live attenuated influenza vaccine (LAIV) in children 2 through 17 years of age. Methods: The study was conducted in 6 large integrated health care organizations participating in the Vaccine Safety Datalink (VSD). Trivalent LAIV safety was assessed in children who received LAIV between September 1, 2003 and March 31, 2013. Eighteen pre‐specified adverse event groups were studied, including allergic, autoimmune, neurologic, respiratory, and infectious conditions. Incident rate ratios (IRRs) were calculated for each adverse event, using self‐controlled case series analyses. For adverse events with a statistically significant increase in risk, or an IRR > 2.0 regardless of statistical significance, manual medical record review was performed to confirm case status. Results: During the study period, 396 173 children received 590 018 doses of LAIV. For 13 adverse event groups, there was no significant increased risk of adverse events following LAIV. Five adverse event groups (anaphylaxis, syncope, Stevens‐Johnson syndrome, adverse effect of drug, and respiratory failure) met criteria for manual medical record review. After review to confirm cases, 2 adverse event groups remained significantly associated with LAIV: anaphylaxis and syncope. One confirmed case of anaphylaxis was observed following LAIV, a rate of 1.7 per million LAIV doses. Five confirmed cases of syncope were observed, a rate of 8.5 per million doses. Conclusions: In a study of trivalent LAIV safety in a large cohort of children, few serious adverse events were detected. Anaphylaxis and syncope occurred following LAIV, although rarely. These data provide reassurance regarding continued LAIV use.